Improving survival of 3760 patients with lymphoma: Experience of an academic center over two decades. (12th April 2020) - Liu, Weiping; Ji, Xinqiang; Song, Yuqin; Wang, Xiaopei; Zheng, Wen; Lin, Ningjing; Tu, Meifeng; Xie, Yan; Ping, Lingyan; Ying, Zhitao; Zhang, Chen; Deng, Lijuan; et al.
Abstract: Background: The treatment outcomes and prognosis of lymphoma are affected by various factors such as hospital types. This study was to describe the temporal trend in the survival of lymphoma in an academic center in China. Methods: A total of 3840 consecutive patients with lymphoma diagnosed between 1996 and 2015 were reviewed. Eighty patients were excluded, and finally, 3760 patients were analyzed in this study. The cohort was divided into four groups according to calendar periods at diagnosis: 1996‐2000, 2001‐2005, 2006‐2010, and 2010‐2015. The overall survival (OS) rates among the four groups were compared. Results: The 5‐ and 10‐year OS for the whole cohort were 62% and 52%, respectively. The 5‐year OS of patient with classic Hodgkin lymphoma (cHL), mature B‐cell lymphoma (BCL), and peripheral T‐cell lymphoma (PTCL) were 79%, 63%, and 50%, respectively. Among mature BCL, the 5‐year OS was highest in follicular lymphoma (77.8%), followed by Burkitt lymphoma (76.5%), marginal zone lymphoma (74.1%), diffuse large B‐cell lymphoma (61.5%), small lymphocytic lymphoma/chronic lymphocytic leukemia (55.1%), and mantle cell lymphoma (44.3%). Among PTCL, the 5‐year OS was highest in ALK+anaplastic large cell lymphoma (79.0%), followed by ALK−anaplastic large cell lymphoma (63.1%), natural killer/T‐cell lymphoma (57.7%), angioimmunoblastic T‐cell lymphoma (34.9%, and peripheral T‐cell lymphoma not otherwise specified (27.6%). Significant improvement in the survival of lymphoma was observed, with the 5‐year OS increasing from 48% in 1996‐2000 to 65% in 2011‐2015 ( P < .001). The 5‐year OS of patients with cHL, mature BCL, and PTCL changed from 55%, 49%, and 41% in 1996‐2000 to 79%, 65%, and 51% in 2011‐2015, respectively ( P values were .014, .002, and .592, respectively). Conclusion: The survival of most types of lymphoma such as cHL and mature BCL, rather than PTCL, was improved significantly during the past two decades. Abstract : Increase in overall survival of lymphoma from 1996 to 2015.